Reverse Immunology Approach to Define a New HIV-gp41-Neutralizing Epitope - Karim Dorgham; Nicolas Pietrancosta; Amel Affoune; Olivier Lucar; Tahar Bouceba; Solenne Chardonnet; Cedric Pionneau; Christophe Piesse; Delphine Sterlin; Pablo Guardado-Calvo; Philippe Karoyan; Patrice Debré; et al. (Journal of Immunology Research)
The design of immunogens susceptible to elicit potent and broadly neutralizing antibodies against the human immunodeficiency virus type 1 (HIV-1) remains a veritable challenge in the course of vaccine development. Viral envelope proteins adopt different conformational states during the entry process, allowing the presentation of transient neutralizing epitopes. We focused on the highly conserved 3S motif of gp41, which is exposed to the surface envelope in its trimeric prefusion state. Vaccination with a W614A-modified 3S peptide induces in animals neutralizing anti-HIV-1 antibodies among which we selected clone F8. We used F8 as bait to select for W614A-3S phage-peptide mimics. Binding and molecular docking studies revealed that F8 interacts similarly with W614A-3S and a Mim_F8-1 mimotope, despite their lack of sequence homology, suggesting structural mimicry. Finally, vaccination of mice with the purified Mim_F8-1 phage elicited HIV-1-neutralizing antibodies that bound to the cognate W614A-3S motif. Collectively, our findings provide new insights into the molecular design of immunogens to elicit antibodies with neutralizing properties.